2006
DOI: 10.1124/jpet.105.096917
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline Improves Early Allograft Function in Rat Kidney Transplantation

Abstract: Several previous studies have demonstrated a beneficial effect of the adenosine receptor (AdoR) antagonist theophylline in different forms of acute renal failure in laboratory animals and in humans. Therefore, we wanted to test whether theophylline can also improve impaired allograft function following ischemia reperfusion injury in experimental kidney transplantation (KT). Orthotopic transplantation of the left kidney was performed from Fisher 344 into Lewis rats. All transplanted rats received daily cyclospo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Thus the dose of DPCPX showed a protective effect in glycerol-induced acute renal failure (20,44), the dose of DMPX had a maximal effect on NECA-induced hypothermia and locomotor activity depression (42), and the dose of MRS 1119 was protective in ischemia-reperfusion and myoglobinuria-mediated renal injury (25). Furthermore, we could show that the dose of theophylline was protective following renal transplantation (14) and that the dose of APCP or PSB 1115 abolished the renal or cardioprotective effects of ischemic preconditioning, respectively (7,15). To provide confidence that the results of this study do not reflect in our hands a lack of sensitivity and/or specificity for the detection of EPO, we refer to our previous investigations showing an increase or decrease of the EPO secretory response in rats following renal denervation or in rats on a high-salt diet, respectively, following 4 h of exposure to 600 ppm CO compared with controls.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus the dose of DPCPX showed a protective effect in glycerol-induced acute renal failure (20,44), the dose of DMPX had a maximal effect on NECA-induced hypothermia and locomotor activity depression (42), and the dose of MRS 1119 was protective in ischemia-reperfusion and myoglobinuria-mediated renal injury (25). Furthermore, we could show that the dose of theophylline was protective following renal transplantation (14) and that the dose of APCP or PSB 1115 abolished the renal or cardioprotective effects of ischemic preconditioning, respectively (7,15). To provide confidence that the results of this study do not reflect in our hands a lack of sensitivity and/or specificity for the detection of EPO, we refer to our previous investigations showing an increase or decrease of the EPO secretory response in rats following renal denervation or in rats on a high-salt diet, respectively, following 4 h of exposure to 600 ppm CO compared with controls.…”
Section: Discussionmentioning
confidence: 88%
“…The doses of all substances that we have tested were based on earlier reports in which clear antagonistic effects were demonstrated on different organ function in experimental animals. We used 8-phenyltheophylline (8-PT) as a nonspecific AR antagonist (10 mg/kg ip) (14) and 8-cyclopentyl-1,3-dipropylxanthine (DPCPX; 1 mg/kg ip) (20,44), 3,7-dimethyl-1-propargylxanthine (DMPX; 1 mg/kg ip) (42), PSB 1115 (10 mg/kg ip) (7), and MRS 1119 (1 mg/kg ip) (25) as specific AR subtype inhibitors. CD73 was inhibited using adenosine 5Ј-(␣,␤-methylene) diphosphate (APCP; 2 mg ip) (7,15).…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of aminophylline for renal protection has been reported in cisplatin- (3), tacrolimus- (4), and contrast-induced (5, 6) AKI, in animal models of kidney transplantation (20), and in the vasomotor nephropathy of very pre-term newborns (21). However, its use in critically ill infants and children is not well described.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, theophylline administered 5 days after ischemia acutely increased renal blood flow and GFR in previously untreated rats (Lin et al 1988). Theophylline also caused an increase of GFR measured 5 days after experimental renal transplantation in rats without affecting the inflammatory response (Grenz et al 2006). On the other hand, in a small study with limited statistical power theophylline was not found to afford protection against acute renal failure during cardiac surgery (Kramer et al 2002).…”
Section: Disease and Therapeutic Aspectsmentioning
confidence: 99%